Desenvolvimento de compósitos biodegradáveis a partir de amido termoplástico e fibras vegetais - Carmona, Vitor Brait (Universidade Federal de São Carlos, 2011)
This project had as main objectives to obtain and to develop new and biodegradable composites from renewable sources using a thermoplastic starch (TPS) matrix reinforced with different amounts of natural fibers, acuri, carandá and gravatá. Initially, these fibers were extracted and characterized, which are still unknown to the scientific community their potential use in composites. The characterization were realized by themorgravimetric analysis (TGA), tensile test, chemical characterization by determination of their main constituents and infrared spectroscopy (FTIR), and morphological and structural analysis by xray diffraction (XRD) and scanning electron microscopy (SEM). The fibers had thermal stabilities similar to each other with their initial temperature of thermal degradation in the range of 250 °C. The fibers show a brittle behavior when subjected to tensile tests, and it were determined elastic moludus and tensile strength in the range of 13 to 50 GPa and 180 to 580 MPa, respectively and, both thermal and mechanical stability are in according to those conventional natural fibers. It was possible to determine the crystallinity index of the fibers by XRD, and SEM images show the fibers surfaces. Four composites formulations were obtained and processed based on four different fibers content (5%, 10%, 15% and 20% w/w), and were evaluated as a function of fiber content water absorption properties, thermal and mechanical stability, and morphological and structural characterization by SEM and XRD. The thermal stability and morphology of TPS homogeneous matrix weren t influenced by the presence of natural fibers, besides the absence of new crystalline structures by XRD. The presence of fibers reduced material water absorption. Mechanical properties such as elastic modulus and tensile strength increased with fiber content, especially at levels above 10% w/w, and the viscosity of the molten also have increased with fiber content. Overall, it was possible to extract and to characterize new natural fibers and use them in a TPS matrix, obtaining new biodegradable composites by conventional processing methods.
Development of biodegradable composites from thermoplastic starch and vegetable fibers
Keywords: Polímeros; Amido termoplástico; Fibras naturais; Compósitos biodegradáveis; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA